2012
DOI: 10.5194/nhess-12-2225-2012
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of intense rainfall events on Madeira Island during the 2009/2010 winter

Abstract: Abstract. This paper constitutes a step towards the understanding of some characteristics associated with high rainfall amounts and flooding on Madeira Island. The high precipitation events that occurred during the winter of 2009/2010 have been considered with three main goals: to analyze the main atmospheric characteristics associated with the events; to expand the understanding of the interaction between the island and the atmospheric circulations, mainly the effects of the island on the generation or intens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
52
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(62 citation statements)
references
References 47 publications
9
52
0
1
Order By: Relevance
“…An official report from the National Weather Service (Guttman, 2010) showed that the heavy rainfall was associated with a plume of deep moisture (Figure 2(a)) which came across the Atlantic Ocean with strong southwesterly flow and passed over Madeira. The plume of moisture is visible in the total precipitable water (Figure 2(a)) obtained from the Atmospheric InfraRed Sounder (AIRS), as explained in Couto et al (2012). It was reported that the precipitable water (PW) anomalies over 42 mm from the 'rum-runner express' were of the order of 4-5 standard deviations above normal (Figure 2(b)).…”
Section: Description Of the Madeira And Associated Rainfall Eventmentioning
confidence: 92%
See 1 more Smart Citation
“…An official report from the National Weather Service (Guttman, 2010) showed that the heavy rainfall was associated with a plume of deep moisture (Figure 2(a)) which came across the Atlantic Ocean with strong southwesterly flow and passed over Madeira. The plume of moisture is visible in the total precipitable water (Figure 2(a)) obtained from the Atmospheric InfraRed Sounder (AIRS), as explained in Couto et al (2012). It was reported that the precipitable water (PW) anomalies over 42 mm from the 'rum-runner express' were of the order of 4-5 standard deviations above normal (Figure 2(b)).…”
Section: Description Of the Madeira And Associated Rainfall Eventmentioning
confidence: 92%
“…They showed that strong humidity convergence at lower levels (at and below 700 hPa) was an important dynamical ingredient that contributed to enhancing upward movements and higher precipitation generation. Couto et al (2012) analysed these events together with the other extreme precipitations events which occurred in the 2009/2010 winter. The authors found that in six out of the seven cases analysed the passage of a cold front and the presence of atmospheric rivers, acting to increase moisture in the lower atmospheric levels, together with the orographic lifting, induced the heavy precipitation events.…”
Section: Introductionmentioning
confidence: 99%
“…The amount of rainfall increases with altitude and the northern slopes are more humid than the southern ones (Prada et al, 2009). Madeira's location, topography and natural vegetation originate a variety of micro-climates, and this Portuguese island has essentially a Mediterranean climate with mild summers and winters (Couto et al, 2012). Some exceptions are found at the highest altitudes, where the mean annual air temperature can decrease to 8 + C, while in the coastal regions it ranges between 18 + C and 19 + C (Lima and Lima, 2009).…”
Section: Study Areamentioning
confidence: 99%
“…During the summer season, the rainfall regime is also affected by the Azores anticyclone (Couto et al, 2012). The island's mountain streams have a high seasonal, torrential flow regime, with high waters during the months of October to March/April (Shahin, 2012) and very low flows during the rest of the year.…”
Section: Study Areamentioning
confidence: 99%
“…On 20 February 2010 an extreme rainfall event followed a prolonged precipitation period (Luna et al, 2011;Couto et al, 2012;Fragoso et al, 2012;Teixeira et al, 2014). In the first hours of the morning rainfall values reached more than the double of the monthly average, triggering landslides and exceptionally strong flash floods that affected severely the municipalities of Funchal (home to half of the island population) and Ribeira Brava (Lira et al, 2013).…”
Section: Study Area and Imagery Data Setsmentioning
confidence: 99%